How safe are standard certified motorcycle safety helmets? Malaysian postal delivery riders scenario - Yellappan, Kaviyarasu; Mani, Kulanthayan K.C.; Mohd Tamrin, Shamsul Bahri (Taylor & Francis, 2019)
Objective: The objective of this study was to determine the proportion of motorcycle safety helmets (MSHs) used by postal delivery riders (PDRs) that comply with the Standards and Industrial Research Institute of Malaysia’s (SIRIM) MSH standard guidelines and identify factors that contribute toward compliance of used MSHs with the standards. Methods: The presence of SIRIM certification label, the status of MSH, type of chinstrap, MSH crash history, and duration of MSH use were observed. The dependent variable was the results of the SIRIM testing procedures (SIRIM tests). MSHs that passed the SIRIM tests were considered “standard certified” MSHs. Results: The odds of the complimentary MSHs passing all of the SIRIM tests were 3.7 times the odds of the self-purchased MSHs passing the tests. The odds of MSHs with the SIRIM certification label passing all of the SIRIM tests were 24.2 times the odds of MSHs without the SIRIM certification label, and the odds of MSHs used <3 years passing the SIRIM tests were 3.75 times the odds of the MSHs used ≥3.8 years. Conclusion: PDRs provided with complimentary MSHs with the SIRIM certification label by the employer for their daily delivery routines and duration of MSH used for less than 3 years were found to be safe MSHs for male occupational riders in Malaysia.